2018
DOI: 10.1186/s12879-018-3487-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent candidemia in very low birth weight neonates: risk factors and clinical significance

Abstract: BackgroundThe prevalence and risk factors for persistent candidemia among very low birth weight infants are poorly understood. This study aimed to investigate the epidemiology of persistent candidemia over a 4-year period in a neonatal intensive care unit (NICU) in Liuzhou, China.MethodsWe retrospectively extracted demographic data, risk factors, microbiological results and outcomes of very low birth weight infants with candidemia in our hospital between January 2012 and November 2015. Persistent candidemia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…Neonatal analyses have demonstrated an association between PC and non‐albicans Candida species 9,11 . Our results reflected no such association in an adult population, consistent with the findings of other studies conducted in adult populations 12,23 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Neonatal analyses have demonstrated an association between PC and non‐albicans Candida species 9,11 . Our results reflected no such association in an adult population, consistent with the findings of other studies conducted in adult populations 12,23 .…”
Section: Discussionsupporting
confidence: 91%
“…The most relevant problem in evaluating PC is the lack of a homogeneous definition of PC 7 . Most studies evaluating PC include adult and child populations or have been conducted only in neonatal populations 2,8‐11 . This complicates any generalisation of the results to adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Age, length of hospital stay, respiratory dysfunction, hospitalisation duration (>30 days), and IC due to C albicans and C glabrata were predictors of mortality in the univariate analysis (P < 0.05). The number and types of prognostic factors in our study differed from those in other epidemiological studies, such as those by Santolaya et al, 19 Liu et al, 26 Chen et al, 27 Sutcu et al, 31 Fu et al, 38 Ishiwada et al, 24 Lee et al 34 and Rodrigues et al 23 Of all the variables that were significantly associated with mortality in the univariate analysis, respiratory dysfunction was the only predictive factor of mortality in the multivariate analysis in our study. The hospital mortality rate in our study was only 8.1% among all paediatric patients with IC, which is substantially lower than the mortality rates reported by Charsizadeh et al (42.5%), 20 Santolaya et al (31.5%), 19 Oeser et al (31.0%), 25 Liu et al (26.3%), 26 Hsu et al (23.7%) 28 and Xia et al (19.3%) 9 and similar to those reported by Chen et al 27 and Mesini et al 21 The mortality rate of neonatal IC in our study was the highest but was similar to that reported by Oncu et al 32 Additionally, the mortality rate (13.0%) in our study was lower than those reported by Charsizadeh et al (42.9%), 20 Santolaya et al (40.0%), 19 Hsu et al (31.8%), 28 Oeser et al (31.0%), 25 Liu et al (26.3%) 26 and Xia et al (19.3%) 9 and higher than that reported by Chen et al 27 In our study, the mortality rate due to non-albicans Candida species was the highest (13.6%, 6/44) but was similar to the rates in most reports, such as those by Charsizadeh et al, 20 Rodrigues et al 23 and Fu et al 8 ; however, our rate differed from that in Lee et al's report.…”
Section: Ta B L E 4 Factors Associated With 60-d Mortality By Multivacontrasting
confidence: 82%
“…16 The same results were revealed in infant patients that persistent candidemia also had a higher incidence of mechanical ventilation (85.7% vs 50.0%; P < .001) and mechanical ventilation had a significantly increased risk of developing into persistent candidemia (OR 5.72, 95% CI 1.05-31.25). 19 Even after prompt removal of infected medical appliances, the residual fungal deposit might exist because Candida species has an ability to adhere to foreign material. 20 We found candida score has a value of Odds Ratio about 6.8.…”
Section: Discussionmentioning
confidence: 99%